TRAFFICKING: SUATU STUDI TENTANG PERDAGANGAN PEREMPUAN DARI ASPEK SOSIAL, BUDAYA DAN EKONOMI DI KABUPATEN BANYUMAS - Muflichah, Hj. Siti; Bintoro, Rahadi Wasi (Jurnal Dinamika Hukum, 2009)
Trafficking  or people commerce is a recruitment, transportation, reception centre, sending, moving or reception somaone with threat, harshness, abduction, forgery, deception, abuse of power, trapping of debt or giving payment or profit, so get approval from people holding to conduct of others, both for conducted in inter-states and state for ceploittation or result people exploited. From understanding above, hence form trafficking can in the form of labor migran legal also illegal, worker of hausehold, worker of commercial seks, wedding orger, spurlous child adoption, beggar, pornography industry, circulation of forbidden drug and sale of body organ. Pursuant to research result, trafficking form that happened Banyumas is expressed. Its for ecample that is husemaid labour of migran and worker of commercial seks. Form of him not yet been expressed. Cause factor the happen of trafficking is economic factor or poorness, education which relative lower, patriakhi culture who then push woman motivate to fulfill requirement of economics and fulfill the him of as especial entrpreneur. The trafficking victims less get protection of law, this matter is caused by law and substanstion regulation completely arrangen protection to victim. The adjacent is theoretically conducted in three aspects, its relocation, repatriating, and reintegration, but not all victims get adjacent pattern. Kata kunci :  trafficking, perlindungan hukum, perantara, korban